Performance investigation of a concentric double tube heat exchanger using twisted tape inserts and nanofluid. (3rd April 2022) - Kundan, Lal; Darshan, M. B.
Abstract: A horizontal double-tube counter-flow heat exchanger with and without twisted tape inserts (twist ratio of 3.2, 4, and 6) has been investigated experimentally using TiO2 -H2 O nanofluid. In this study, the heat transfer coefficient and friction factor of turbulent flow of TiO2 -H2 O nanofluid have been determined for Reynolds' number varying from 5, 000 to 25, 000. Convective heat transfer coefficient for TiO2 -H2 O nanofluid (0.05% by vol.) is found to be higher than base fluid (4–6%). Also, an increase in the heat transfer coefficients up to 6%, 10.9%, 17.4%, and 23.4% are observed numerically for the 0.05%, 1%, 2%, and 3% volume concertation of nanoparticles of TiO2 . On the other hand, when TiO2 -H2 O nanofluid (0.05% by vol.) is investigated using twisted tape inserts of twist ratio 3.2, the heat transfer coefficient is found to be increasing by 45%. The variation of the heat transfer coefficient for different types of nanofluids such as; TiO2 -H2 O, Al2 O3 -H2 O, and CuO-H2 O with 1% concentration of nanoparticles (by vol.) has also been studied at different Reynolds' numbers. The simulated results show no significant effect of the size (30 nm and 50 nm) of nanoparticles (TiO2 ) on the heat transfer coefficient values of TiO2 -H2 O nanofluid at 0.05% volume concentration.